Review of Phytochemicals and Its Biological Activities and Contemporary Nutraceuticals - Laode Rijai (Journal of Tropical Pharmacy and Chemistry, 2019)
Nutraceutical is food for health with functions of preventive, promotive, rehabilitation, aesthetic, intelligence to curative. Nutraceuticals as food products can have a contemporary value, which is a trend or extraordinary circumstance that attracts consumers because of its function as a supplement, functional food, medical food, and genetically engineered food so that it penetrates the world market without limits. Nutraceuticals that are contemporary make it easy to achieve the goals of health care by using the "nutraceuticals" approach because the client wishes to himself with a high level of confidence in the benefits of the product for health and therefore uses it. Potential compound for nutraceuticals is secondary metabolites because it has multipotential for health, but specific to certain functions. Secondary metabolites, generally sourced from low plants and animals, because these biological groups do not have a perfect secretion system so that metabolites resulting from secondary metabolism are stored in cells and tissues properly, with several functions, among others, for defense and attractiveness of the biological. Some of the classes and compounds of plant secondary metabolites that are known to have potential for nutraceuticals are Terpenoids, Terpenoids non-Carotenoids, Polyphenolics, Phenolic Acids, Non-Flavonoid Polyphenolics, Glucosinolates, Thiosulphinates, Phytosterols, Anthraquinones, Glucosamines, Octacosanolines, Characticines, Chines) Pectin, Pigments, Tocotrienols and Tocopherols, Ubiquinon and ?-Lipoic Acid. Furthermore, some contemporary nutraceuticals are Spiruline, Broccoli, Aloe Vera Gel and Aloe Juice, Soyfoods, Omega-3- Fatty Acids, Pomegranate Juice, Walnuts, and Organic Mushroom Nutrace.